PENETAPAN SATU PASANGAN CALON DALAM PEMILIHAN UMUM KEPALA DAERAH KABUPATEN BADUNG TAHUN 2020 SEBAGAI IMPLEMENTASI PEMILU BERINTEGRITAS - Wedanti, I Gusti Ayu Jatiana Manik (Institut Hindu Dharma Negeri Denpasar, 2021)
The implementation of the regional head general election in the context of the election of the Regent and Deputy Regent in Badung Regency in 2020 then recorded the first history in the implementation of the regional head general election simultaneously in Bali Province, namely the determination of one candidate pair as the only participant participating in the regional head general election held in Badung Regency in 2020. This is certainly interesting to analyze so that in this paper it will be analyzed and described the relationship between elections with integrity and the determination of a single candidate in the general election for the regional head of Badung Regency in the simultaneous regional head elections in 2020. This writing uses normative legal research methods. Where in this paper, we use statutory studies and literature to analyze the determination of a single candidate in the regional head elections in Badung Regency in the context of the election of the Regent and Deputy Regent in 2020. The results of the analysis carried out were the determination of one candidate pair in the general election of the Regent and Deputy Regent in Badung Regency by the KPU of Badung Regency has been following the basic legal provisions of the implementation of regional head elections and the determination of one candidate pair in the regional head general election for the election of regents and deputy regents in Badung Regency in 2020 and has fulfilled the principles of elections with integrity, namely the general election of the head regions must continue to be implemented even though there is only one pair of participants participating in the regional head election competition so that the political rights of citizens to be able to elect their leaders based on the principles of democracy are fulfilled the elected leader is expected to be able to carry out the task us and its obligation to prosper and protect its people.Keywords: Election for regional heads, Election with Integrity, One Candidate Pair, Democracy